Digitalization of Payments and Financial Management for MSMEs at Warkop Gondrong Makassar - M. Yusuf K; Sri Wahyuni; Ismawati; Muh. Khaidir Ramadhan; ⁠Ahmad Izzaturrahim (Masterpiece, 2025)
The community service project with the theme UMKM GO DIGITAL: "Digitization of Payments and Financial Management of Warkop Gondrong Makassar" aims to provide socialization to UMKM actors, about the urgency of digitalization as one of the supporters of competitiveness in the small business market, and also as a representative of public complaints regarding counterfeit money whose circulation in South Sulawesi until now has not been controlled according to the statement of the South Sulawesi Regional Police Chief, Inspector General Yudhiawan Wibisono, which was published in the Detiksulsel media. In a press conference, on Monday (12/30/2024). Therefore, it is hoped that this activity can minimize the impact of the case on UMKM actors. We carried out this activity at Warkop Gondrong, Jalan Tinumbu, Makassar City. By involving a committee of approximately 21 people, and participants of approximately 13 participants . Through this community service, we have a target to be able to provide socialization about how important the role of digitalization is in supporting MSME businesses, and also as a step to reduce public anxiety about issues that have recently gone viral. When payments have been made using a digital system, it is considered that it can reduce the impact of the spread of counterfeit money. By using Qris as a media or transaction tool, it is more effective and efficient.